Pengaruh Good Corporate Governance dan Corporate Social Responsibility terhadap Kinerja Keuangan (ROA) - Nugrahani, Tri Siwi; Susanti, Lisa; Junaidi; Purnama, Hari; Lestari, Tias Budi (Universitas PGRI Yogyakarta, 2025)
The development of the company cannot be separated from governance, especially related to the achievement of financial performance. Similarly, for 45 companies as a sample of this study, using the purposive sample method, namely companies listed on IDX in 2020-2022 and companies that compile Corporate Social Responsibility reports. This study proves that governance such as the board of directors and the audit committee play a significant role in determining the company's strategy, including financial performance. In addition, the corporate social responsibility activities disclosed are also able to affect the company's financial performance. However, corporate governance in the form of independent commissioners and institutional shareholding is not able to affect financial performance. This study is limited to mining companies, so it is necessary to re-test in other sectors to compare whether or not the results are consistent with governance and CSR issues related to financial performance.